Factors Affecting Supplier Managed Inventory (SMI) Implementation - TAN, BEE NAH (2004)
A major impediment to efficient supply chain integration is the cost of managing inventory. Due to the need to create efficiencies in the supply chain by targeting this “inventory” link, the concept of Supplier Managed Inventory (SMI) was born. However, most of the research has focused on the grocery industry and large companies. There is a lack of studies on the factors that affect the success of SMI programs in manufacturing industry.